THE BICYCLIST SAFETY ANALYSIS BASED ON ROAD INCIDENTS MAPS - Elżbieta MACIOSZEK; Agata WYDERKA; Irena JURDANA (Scientific Journal of Silesian University of Technology. Series Transport)
Increasing road congestion leads to frustration and irritation of drivers, which often contributes to dangerous driving maneuvers. This causes dangerous situations - collisions or road accidents. The driver, while moving the car, is protected by the vehicle body and, above all, by the crumple zone. Unprotected road users, such as pedestrians or cyclists, usually do not have any protection. The article aims to assess the state of bicycle traffic safety in the Małopolskie Voivodeship in 2012-2019. This assessment was made based on road incident maps. In the first stage of work, the indicators for the number of incidents per 1 million inhabitants and the severity of the incidents were calculated for the entire Małopolskie Voivodeship and particular counties in 2012-2019. The data from the Accident and Collision Record System and the Central Statistical Office were used for this purpose. Then, the safety of bicycle traffic in the Małopolskie Voivodeship was analyzed based on the developed road incident maps. Although the number of road incidents increases from year to year in the analyzed period, they are less severe over time. Presenting road incidents data on maps allows for the highlighting of critical locations on the city's transport network from the point of view of cyclists' safety.